Facile Conversion of syn‐[FeIV(O)(TMC)]2+ into the anti Isomer via Meunier's Oxo–Hydroxo Tautomerism Mechanism. (17th January 2019) - Prakash, Jai; Sheng, Yuan; Draksharapu, Apparao; Klein, Johannes E. M. N.; Cramer, Christopher J.; Que, Lawrence
Abstract: The syn and anti isomers of [Fe IV (O)(TMC)] 2+ (TMC=tetramethylcyclam) represent the first isolated pair of synthetic non‐heme oxoiron(IV) complexes with identical ligand topology, differing only in the position of the oxo unit bound to the iron center. Both isomers have previously been characterized. Reported here is that the syn isomer [Fe IV (O syn )(TMC)(NCMe)] 2+ (2 ) converts into its anti form [Fe IV (O anti )(TMC)(NCMe)] 2+ (1 ) in MeCN, an isomerization facilitated by water and monitored most readily by 1 H NMR and Raman spectroscopy. Indeed, when H2 18 O is introduced to2, the nascent1 becomes 18 O‐labeled. These results provide compelling evidence for a mechanism involving direct binding of a water molecule trans to the oxo atom in2 with subsequent oxo–hydroxo tautomerism for its incorporation as the oxo atom of1 . The nonplanar nature of the TMC supporting ligand makes this isomerization an irreversible transformation, unlike for their planar heme counterparts.